Rv2969c, essential for optimal growth in Mycobacterium tuberculosis, is a DsbA‐like enzyme that interacts with VKOR‐derived peptides and has atypical features of DsbA‐like disulfide oxidases. (8th October 2013) - Premkumar, Lakshmanane; Heras, Begoña; Duprez, Wilko; Walden, Patricia; Halili, Maria; Kurth, Fabian; Fairlie, David P.; Martin, Jennifer L.
<x xml:space="preserve">Abstract</x> The bacterial disulfide machinery is an attractive molecular target for developing new antibacterials because it is required for the production of multiple virulence factors. The archetypal disulfide oxidase proteins in Escherichia coli (Ec) are DsbA and DsbB, which together form a functional unit: DsbA introduces disulfides into folding proteins and DsbB reoxidizes DsbA to maintain it in the active form. In Mycobacterium tuberculosis (Mtb), no DsbB homologue is encoded but a functionally similar but structurally divergent protein, MtbVKOR, has been identified. Here, the Mtb protein Rv2969c is investigated and it is shown that it is the DsbA‐like partner protein of MtbVKOR. It is found that it has the characteristic redox features of a DsbA‐like protein: a highly acidic catalytic cysteine, a highly oxidizing potential and a destabilizing active‐site disulfide bond. Rv2969c also has peptide‐oxidizing activity and recognizes peptide segments derived from the periplasmic loops of MtbVKOR. Unlike the archetypal EcDsbA enzyme, Rv2969c has little or no activity in disulfide‐reducing and disulfide‐isomerase assays. The crystal structure of Rv2969c reveals a canonical DsbA fold comprising a thioredoxin domain with an embedded helical domain. However, Rv2969c diverges considerably from other DsbAs, including having an additional C‐terminal helix (H8) that may restrain the mobility of the catalytic helix H1. The enzyme is also characterized by a very shallow hydrophobic binding surface and a negative electrostatic surface potential surrounding the catalytic cysteine. The structure of Rv2969c was also used to model the structure of a paralogous DsbA‐like domain of the Ser/Thr protein kinase PknE. Together, these results show that Rv2969c is a DsbA‐like protein with unique properties and a limited substrate‐binding specificity.